Zika virus knowledge, contraception use, and lessons learned from a Dominican Republic pilot study. Issue 3 (12th September 2019) - Shaw, Rebecca; Baker, Elizabeth; Jie, Chunfa; Adamian, Shant; Andres, Sarah; Bachelor, Brooke; Hodges, Fiona; Mittra, Tricia; Viloria, Anny Rodriquez
Abstract: Objective: To assess knowledge of the Zika virus (ZIKV), use of contraceptives, and sources of health information in rural communities in the Dominican Republic. Methods: Over 4 days in March 2017, a research team traveled to four rural communities in the Dominican Republic to provide healthcare services. Overall, 90 men and women consented to a voluntary verbal 12‐question survey. Results: Of the participants, 55% were not certain whether ZIKV is transmitted sexually; 75% of participants were either not sure or thought ZIKV was not present in their community. Charlas (informal discussions led by community health workers) were cited as the most common source for public health information. Prevalence of contraceptive use was 26.6% hormonal and 1.1% long‐acting reversible contraception (LARC); 30.0% cited no use of contraception. Conclusion: Significant deficits in ZIKV knowledge, underutilization of LARCs, and socioeconomic factors exist that constrain the application of WHO recommendations for preventing ZIKV infection. Additional and more robust surveys are needed to assess public health education and interventions, critical for disease prevention in communities facing current and future epidemics. Abstract : Rural Dominican Republic communities are at risk for Zika virus sequelae due to a lack of accurate knowledge and reliable contraception.